2013
DOI: 10.1186/1916-0216-42-31
|View full text |Cite
|
Sign up to set email alerts
|

Primary surgery versus chemoradiotherapy for advanced oropharyngeal cancers: A longitudinal population study

Abstract: BackgroundTreatment for advanced stage oropharyngeal squamous cell carcinoma (OPSCC) includes combined chemoradiation therapy or surgery followed by radiation therapy alone or in combination with chemotherapy. The goal of this study was to utilize available evidence to examine survival outcome differences in patients with advanced stage OPSCC treated with these different modalities.MethodsPatients with advanced stage OPSCC were identified. Primary outcome measurements were disease specific and overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 37 publications
(33 reference statements)
1
37
2
Order By: Relevance
“…Patients with tumors at stage IV treated with chemoradiotherapy presented poor survival in our study, as previously reported (O'Connell et al 2013). In addition, we observed, for the first time, that OPSCC patients with tumors at stage IV and OGG1 c.977CC wild-type genotype had worst PFS when compared with carriers of variant allele.…”
Section: Discussionsupporting
confidence: 88%
“…Patients with tumors at stage IV treated with chemoradiotherapy presented poor survival in our study, as previously reported (O'Connell et al 2013). In addition, we observed, for the first time, that OPSCC patients with tumors at stage IV and OGG1 c.977CC wild-type genotype had worst PFS when compared with carriers of variant allele.…”
Section: Discussionsupporting
confidence: 88%
“…In comparison to our centre’s previously published results, we found that the percentage of patients undergoing RT alone was not as high (18.3% in previous results vs 3% in this cohort) [2]. This likely reflects the fact that patients receiving RT alone was likely palliative, and these patients should have been removed from the previous study.…”
Section: Discussioncontrasting
confidence: 76%
“…Some studies have shown equivalent outcomes, 5 whereas others clearly demonstrate superior survival with primary surgical approaches. 16,17 There have also been some retrospective historical 18 and case control 19,20 studies showing similar survival outcomes from these approaches. Moreover, preliminary results of transoral approaches are showing survival data comparable to that of primary CRT protocols.…”
Section: Introductionmentioning
confidence: 99%